Leadership style in knowledge-based culture: The competitive advantage approach - Abd Ghani, Noor Hasmini; Mohamad, Osman; Mohamed Anuar, Marhana (2007)
In nowadays economy, knowledge becoming the primary bases of core competency and key to superior performance. Several reasons are advanced for the implementation of knowledge management (KM) within companies. These includes of the widespread digitalisation of business environments; the rise of time-based competition that require firms to learn as much as possible in very short periods; the globalization of operations; and the high incidence of mergers and takeovers. Thus, for these reasons, it is crucial for a company to explore any factors that can enhance the knowledge-based organization. The proper way in managing the knowledge will lead to firm’s competitive advantage achievement. In this paper, the leadership styles as important factors in enhance the practices of knowledge-based culture will be the main focused. Specifically, this paper is to address three main objectives. First objective is to discuss the important of leadership styles in association to organizational learning culture, the most excellent principal in order to manage and value knowledge. Secondly, this paper will explain the important of leadership styles in firm’s competitive advantage achievement. And lastly, this paper will further discuss the important of leadership role in inter-firm settings and it relationship to competitive advantage.